Գլխուղեղի կաթվածից հետո դեֆիցիտի արտահայտվածությունը քրոնիկական սրտային անբավարարությամբ բուժառուների շրջանում - Հակոբջանյան, Վ. Գ. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В исследование были включены 60 пациентов: 30 женщин и 30 мужчин. Всем пациентам была проведена МРТ головного мозга, ЭхоКГ, ОАК, ОАМ, БAK, ЭКГ. Пациенты были разделены на 2 группы: 1. ФВ <40; 2. ФВ 41-49. У всех пациентов был ФП (перманент), СД 2, ишемический инсульт кардиоэмболического генеза. Цель данного исследования – показать, что неврологический дефицит сохраняется дольше у пациентов с низкой ФВ, чем у пациентов с умеренной ФВ. (RR-1,5714, CI 95%-1,0129-2,4381, p=0,04): This study lasted 6 months. The study included 60 patients ≥65 years of age, 30 women and 30 men. All patients underwent magnetic resonance imaging (MRI) of the brain, which confirmed ischemic stroke, echocardiography, TBC. Blood chemistry tests, total urine analysis, ECG. The neurological deficit in patients was assessed using the NIHSS table. The echocardiographic picture in patients was as follows: left atrial size ≥40 mm, mitral regurgitation II, for both groups. Patients were divided into two groups: 1. Type 2 diabetes, AF, permanent, systolic heart failure with an ejection fraction of < 40. 2. Type 2 diabetes, AF, permanent, cardiac failure with a mean ejection fraction of 41-49. Conclusion: the aim of the study was to assess and compare the presence of deficit in patients with chronic heart failure based on ejection fraction, with a particular emphasis on the group of patients with low EF. The analysis shows that the presence of deficit was more pronounced in the group of patients with low EF (RR-1,5714, CI 95%- 1,0129-2,4381, p=0,04).
Keywords: Կլինիկական բժշկություն